Assessing the impact of anthropogenic and natural factors on soil-related ecosystem services: a case study of the coastal landscape of Djibouti - Nikiforova, Aleksandra; Tabunshchik, Vladimir; Pham, Cam Nhung; Chernyi, Georgii; Lineva, Nastasia; Gorbunov , Roman; Gorbunova, Tatiana; Repetskaya, Anna (Brawijaya University, 2025)
Coastal regions are highly sought after for human habitation, exhibiting a population density that is threefold greater than the global mean. These zones are pivotal for environmental resources, human prosperity, and economic activities, providing a suite of services. The concept of ecosystem services has garnered international focus for its contribution to sustainable development. These services represent the myriad benefits that ecosystems confer, meeting socio-economic demands and enhancing human welfare. This analysis endeavors to appraise the value of ecosystem services in coastal areas, with a particular emphasis on the physicochemical properties of soils along Djibouti's coastline. It incorporates an assessment of local characteristics, climatic conditions, and the anthropogenic influence on the environment. Despite facing considerable threats to its biodiversity, Djibouti's coastline offers a plethora of vital ecosystem services to its inhabitants. Among the regulatory services rendered by these locales are air quality management, erosion mitigation, soil and sediment retention, climate and microclimate stabilization, carbon storage and sequestration, nutrient recycling, and facilitation of pollination.